THE EFFECT OF MANAGEMENT CHARACTERISTICS ON STOCK PRICES OF FOOD AND BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2015-2020 PERIOD) - Magdalena Magdalena; Temy Setiawan (INQUISITIVE : International Journal of Economic, 2021)
Economic growth in Indonesia is influenced by various industrial sectors. The industrial sector that has a significant influence on Indonesia's economic growth is the food and beverage industry. The purpose of this study was to determine the effect of Return on Assets, Debt To Equity Ratio, Change of Directors, Women's Leadership, Generation Z and Family Leadership on stock prices of food and beverage companies listed on the Indonesia Stock Exchange for the period 2015 to 2020. The research sample consists of 12 companies. The analytical technique used in this research was to use the Smart PLS (Partial Least Square) software. The results found that Return on Assets, Debt To Equity Ratio, Change of Directors, Generation Z and Family Leadership have a significant influence on stock prices. meanwhile